Investigating Seasonal Patterns in Developing Countries: The Case of FYROM Stock Market - Georgantopoulos, Andreas; Tsamis, Anastasios (International Journal of Economics and Financial Issues, 2011)
This paper uses a data set from FYROM Stock Exchange to investigate the presence of calendar effects in this recently organised equity market during the period 2002–2008. Five well known calendar effects are examined by both mean (OLS) and variance (GARCH) regressions; the day of the week effect, the January effect, the half month effect, the turn of the month effect and the time of the month effect. Results indicate that two of the tested calendar effects are present in the MSE (day of the week and January effects) and conclusions using linear and various GARCH methodologies, always converged to the same results. This survey’s evidence are in line with the majority of similar research which report that calendar effects are still present especially in developing equity markets. However, considering the low level of liquidity and maturity of this market, we would expect more effects to appear significant. Keywords: Calender anomalies; Mena stock returns; Volatility; FYROM JEL Classifications: C32; G10